2013
DOI: 10.1103/physrevb.88.014107
|View full text |Cite
|
Sign up to set email alerts
|

Stability and superconductivity of Ca-B phases at ambient and high pressure

Abstract: In the search for MgB2-like phonon-mediated superconductors we have carried out a systematic density functional theory study of the Ca-B system, isoelectronic to Mg-B, at ambient and gigapascal pressures. A remarkable variety of candidate high-pressure ground states have been identified with an evolutionary crystal structure search, including a stable alkaline-earth monoboride oI8-CaB, a superconductor with an expected critical temperature (Tc) of 5.5 K. We have extended our previous study of CaB6 [Phys. Rev. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 77 publications
3
33
0
Order By: Relevance
“…However, the pressure behavior of the binary systems (Ca-B, Ca-H, B-H), which form the edge of the ternary hull, was studied by ab-initio calculations in recent years, in search for possible superconductors. Superconducting structures were found in all three systems, with a maximum T c of 235 K in CaH 6 and 21 K in BH, both above 150 GPa, and 6 K in CaB at 30 GPa [39,64,65].…”
Section: Phase Diagrammentioning
confidence: 86%
“…However, the pressure behavior of the binary systems (Ca-B, Ca-H, B-H), which form the edge of the ternary hull, was studied by ab-initio calculations in recent years, in search for possible superconductors. Superconducting structures were found in all three systems, with a maximum T c of 235 K in CaH 6 and 21 K in BH, both above 150 GPa, and 6 K in CaB at 30 GPa [39,64,65].…”
Section: Phase Diagrammentioning
confidence: 86%
“…The oI8 structure with zig-zagged B chains metastable in this case was predicted to be thermodynamically stable for the related CaB binary 50 . The instability of hP4-LiB 1D has been associated with a large DOS(E F ermi ) which can be lowered by change in stoichiometry 17 or the proposed distortion at high pressures (Figs.…”
Section: Stability Analysis and Prediction Of Derived Phases Witmentioning
confidence: 86%
“…Unexpectedly, our frozen phonon calculations 39,40 revealed that the family of Li 2n B 1D m phases across a large composition range becomes dynamically unstable under moderate pressures, a behavior not recognized in previous ab initio studies 17,[27][28][29][30]47,48 . Construction of most stable derived structures is a known challenge due to the possibility of multiple local minima with similar energies/enthalpies 43,49,50 . We carefully examined relevant stoichiometries with 1/2 ≤ x ≤ 4/7 under relevant (P, T ) conditions and identified several dynamically stable derivatives.…”
Section: Stability Analysis and Prediction Of Derived Phases Witmentioning
confidence: 99%
“…31,32 Magnesium borides also find use as part of lightweight composite materials and in the thermoelectric properties of borides for systems like MgB 4 , MgB 7 , and other binary alloys. [33][34][35][36][37][38][39][40] The purpose of this work is to investigate the atomic and electronic structure, stability, and reactivity of B n Mg m − clusters containing up to 15 B and up to 3 Mg atoms. The ultimate objective is to identify clusters that could serve as a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%